THE ANALYSIS OF THE MARKETING ACTIVITIES OF DESTINATION MANAGEMENT ORGANISATIONS IN SLOVAKIA - Palenčíková, Zuzana; Mazúchová, Ľudmila (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
Destination management organizations are key players in the destination management and marketing as they have active relationship with the supply and demand side. The aim of the study is to examine marketing activities and tools used by Slovak destination management organisations in purpose to attract targeted segments of visitors and to improve destination competitiveness. Results of field research in Slovakia, realized in summer season 2018, are employed, as well as the survey draws on multiple secondary sources of information. Study provides the empirical framework for identifying the key destination marketing processes and activities in the tourist regions of Slovakia.